2016
DOI: 10.3109/00365513.2015.1137351
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic erythropoietin response in cirrhosis

Abstract: We found no significant differences in EPO concentrations across the liver, kidney, or peripheral circulation in the patient or control groups; and no significant correlations to clinical, biochemical, or hemodynamic characteristics. This suggests that hepatic EPO synthesis is not enhanced in cirrhosis, but larger scale studies are needed to clarify this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In fact, hypoxia is capable of connecting a variety of signals. It not only affects the activation of HSCs but also acts on a variety of other cells, such as sinusoidal cells, hepatocytes, adipocytes, and liver-resident macrophages (Kuppfer cells) [ 1 , 22 24 ]. Secondly, hypoxia-induced structural changes in hepatic fibrosis aggravate the hypoxic environment, thus, in turn, accelerating its pathologic progression of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hypoxia is capable of connecting a variety of signals. It not only affects the activation of HSCs but also acts on a variety of other cells, such as sinusoidal cells, hepatocytes, adipocytes, and liver-resident macrophages (Kuppfer cells) [ 1 , 22 24 ]. Secondly, hypoxia-induced structural changes in hepatic fibrosis aggravate the hypoxic environment, thus, in turn, accelerating its pathologic progression of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of human cirrhotic liver tissue samples, we see enhanced expression of both, EPO and hEPOΔ3. Although elevated blood EPO concentrations are not generally found in patients with cirrhosis 32, 67 , local hepatic tissue hypoxia occurs in patients with cirrhosis 68 . Thus, enhanced EPO and hEPOΔ3 expression in liver cirrhosis is likely explained by hypoxic mechanisms and the observed parallel enhancement in individual samples implies that EPO and hEPOΔ3 transcript expression are co-regulated in vivo .…”
Section: Discussionmentioning
confidence: 98%
“…EPO is a hormone that stimulates the bone marrow to produce red blood cells (RBCs). 43 The main site of EPO production in humans shifts from the liver during fetal development to the kidney after birth. In healthy human adults, renal production of EPO accounts for >90% of circulating EPO.…”
Section: Section 4: Erythropoietin Productionmentioning
confidence: 99%
“…In healthy human adults, renal production of EPO accounts for >90% of circulating EPO. 43 While hepatic synthesis of EPO can increase in states of renal failure, this increase is not sufficient to prevent anemia. 44 Several groups have reported that baboons develop anemia following pig kidney xenotransplantation, which is treated with exogenous EPO.…”
Section: Section 4: Erythropoietin Productionmentioning
confidence: 99%